Microvascular reconstruction with fibula flap: Case Report - Cáceres-Quevedo, Stephanie (2017)
Patient male of 10-year-old native of the city of Puno, arriving at the service of head and neck surgery from the National Institute of health of the child to present an expansive left mandibular tumor of 2 years of evolution of insidious onset and progressive course. Compatible with Desmoplastic fibroma diagnosis. Resection of mandibular tumor, up to 10 cm in length, was practiced the hemimandibulectomy since the region right up to the preangular area of the jaw. During this surgical procedure the flap of the fibula, was conducted on the same side as the hemimandibulectomy. Once the fibula osteotomy was performed to rebuild the receptor bed with unilock reconstruction plates and was fixed with screws. Finally the anastomosis was carried out. One of the greatest challenges of the reconstructor surgeon is the coverage of complex defects in extremities, with exhibition of deep tissues and sometimes with absence of them. As described in the literature, the closure of fibula flap is the